The Art of Audit. Eight remarkable government auditors on stage - Roel Janssen (Amsterdam University Press, 2015)
Accountability, good government and public trust are intricately linked. Supreme Audit Institutions fulfil an exceptional role in the public domain, checking if governments spend their money properly. They are like "watchdogs" for citizens and parliaments with the purpose of auditing public expenditure and examining the effectiveness of policies. They aim to strengthen the trustworthiness of government institutions, all the more so in fragile democracies. They do so, for instance, in striving to disclose cases of corruption, not just in the highest echelons of government, but also in everyday petty bribery. And they can be found counting houses, roads and water taps, to see if government's promises are being kept. On the occasion of the retirement of Saskia J. Stuiveling as the president of the Netherlands Court of Audit, eight (former) heads of audit institutions talk candidly about their work and innovations in the area of public auditing, about how the financial crisis affected their profession, about the advent of open data and about the need for new skills to audit the oil industry. Each of them - Faiza Kefi (Tunisia), Josef Moser (Austria), Terence Nombembe (South Africa), Heidi Mendoza (Philippines), Alar Karis (Estonia), David Walker (USA), John Muwanga (Uganda) and Abdulbasit Turki Saeed (Iraq) - has made a difference in his or her country, often under difficult, adverse and sometimes outright dangerous circumstances.
Keywords: 330; Economy